Characterisation of the Average Worker Employed Under Flexible Forms of Employment –Report on the Study of Individual Differences in the Context of Sociodemographic DataConcerning Polish Workers - Dobrowolska, Małgorzata; Paruzel-Czachura, Mariola; Stasiła-Sieradzka, Marta; Sikora, Jagoda (European Journal of Economics and Business Studies, 2018)
The paper presents the sociodemographic data obtained as a result of an empirical study carried out on a group of n=2118 workers employed under what is referred to as flexible forms of employment, within a more extensive research project entitled “Occupational problems of individuals working under flexible forms of employment – the psychological perspective”. The inspiration to focus on this particular part of the research was provided by a trend observed in the international literature, analysing the profile of an average flexible worker in highly developed countries. An analysis of the study sample of flexible workers shows that the group included rather young people, with a similar share of women and men, living in big cities, and with a rather short length of service; they were well-educated, married people with children, with a small number of previous employers, and mostly working in the private sector. The Polish study sample matches the descriptions of the average flexible European worker.